(untitled) (Global Journal of Human-Social Science, 2023)
This article presents a review of the perception of insecurity and crime incidence in Mexico in recent years In addition the conceptualization that the Political Constitution of the United Mexican States has regarding public safety and the objectives set out in the National Development Plan is reviewed The article also reviews the work carried out by the Citizen Security Commission of the Federal Congress and the budget for public security which is assigned to different federal branches and agencies